ANALISIS FAKTOR-FAKTOR YANG MENYEBABKAN PENUMPUKAN PENCAIRAN DANA APBN DI AKHIR TAHUN (STUDI KASUS DI KPPN MALANG) - Nugroho, Mashudi Adi; Ananda, Candra Fajri (Jurnal Ilmiah Mahasiswa FEB, 2013)
The Government expenditures element of the national budget (besides consumptions and investations) is an element that can boost the economic growth. By increasing amount of government expenditures year to year, naturally it should have positive impact on economic growth. But it could happen if the absorption of government expenditures run stably year-round. In fact, the disbursement of government expenditures (disbursement of national budget) tend to below in the beginning of fiscal year and tend to be accumulated at the end of the fiscal year. Such cumulation can also be seen at Treasury Office of Malang, as a palce where national budget disbursed. The aim of this study is to find out factors causing the accumulation  of  national budget disbursement at the end of the year at at the Treasury Office of Malang. The result of study showed that the accumulation  of  national budget disbursement at the end of the year occured at Treasury Office of Malang caused by 6 factors, namely planning factors, regulatory factors, human resources factors, technical factors, coordination constraints factors, and procurement factors. Moreover, there are also indications that existing administrative requirements have not been able to move synchronously with the fastness of disbursement. It is proved from the tendency of working unit to prioritize the completion of administrative requirements in the disbursement of national budget than the fastness and accuracy of national budget disbursement.Keywords : national budget, disbursement, accumulation